Sustainability assessment for an offshore coral reef island based on scenario simulation and emergy analysis - Wu, Wenzhou; Zhang, Peng; Jiang, Huiping; Su, Fenzhen (Frontiers in Marine Science, 2023)
As the intensity of ocean spatial exploitation increases, the offshore island tourism has been thriving, and the utilization of uninhabited islands is attracting more and more attention. In order to achieve the sustainable development of offshore island tourism resources, it is important to evaluate population carrying capacity and conduct sustainability assessment for uninhabited islands. To this end, we proposed a quantitative evaluation method for the sustainable development of offshore coral reef islands based on the combination of scenario simulation and emergy analysis. This method was tested on a coral reef island in the South China Sea, namely Lingyang Reef. The dynamics in emergy related structures and indicators of Lingyang Reef system were revealed under different scenarios, providing decision-making references for the pre-development sustainability assessment of an uninhabited coral reef island. The evaluation results showed that (1) when accommodating 2000 persons, the island system was in a low-load state, with sustainable values in terms of renewable energy input percentage, environmental load ratio, and emergy sustainability index, except for the critical state of emergy yield ratio; (2) when accommodating 5000 persons, the emergy yield ratio was in an unsustainable state, with the emergy sustainability index in a critical state, and both of the renewable energy input percentage and environmental load ratio in sustainable states, indicating that socioeconomic activities were not beyond the carrying capacity, and the development and utilization intensity was moderate; (3) when accommodating 10000 persons, the renewable energy input percentage and emergy sustainability index were in critical states, and the emergy yield ratio and environmental load ratio were in unsustainable states, indicating that the corresponding human activities had exceeded the carrying capacity.